Fast automated method for the direct determination of total antimony in grape juice samples by hydride generation and atomic fluorescence spectrometric detection without external pretreatment. (1st July 2022) - Lima, Eduardo A.; Cunha, Francisco A.S.; Oliveira, Maria J.; Lyra, Wellington S.; Junior, Mario M.S.; Santos, Josué C.C.; Ferreira, Sergio L.C.; Araujo, Mario C.U.; Almeida, Luciano F.
Highlights: Efficient and reliable acidic antimony extraction in grape juice. Direct determination of total Sb without sample decomposition step. Fast sample processing and reliable determination of total Sb by AFS. No prior sample pretreatment is required. Low residue generation, high accuracy and high sensitivity. Abstract: Matrix complexity of fruit juices and their low antimony level requires sensitive, cost-effective instruments, time-consuming and error-prone sample pretreatment methods. Therefore, a flow-batch procedure (HG-FBA-AFS) was developed for the fast and sensitive determination of total inorganic Sb in grape juice samples by hydride generation atomic fluorescence spectrometry. The sample pretreatment, pre-reduction and stibine formation steps run through the mixing chamber. The HCl and NaBH4 concentrations, and carrier gas flowrate were optimized through a Box-Behnken design. The detection limit (LOD) was 20 ng L −1, intra and inter-day precision ranged in 3.0 – 3.5 %, and low errors within (- 2.4 to 6.6 %) for samples containing 1.23 – 4.58 µg L −1 total Sb. Both HG-FBA-AFS and reference method agreed at 95% confidence level. An 87 h −1 sample throughput, and a 1.15 mL total waste per determination attest that HG-FBA-AFS is a fast, and ecofriendly tool for determining Sb in grape juices.